Application of Deep Breathing Relaxation and Progressive Muscle Relaxation to Reduce Nausea, Vomiting Post Chemotherapy Patients - Khofifah, Siti; Sumarni, Tri; Winahyu, Graytika (PROMOTOR, 2024)
Chemotherapy is one of the treatments most often used in patients with cancer, nausea, vomiting can occur as a side effect, deep breathing relaxation and progressive muscle relaxation can reduce the intensity of nausea. The aim of this research is to apply deep breathing relaxation therapy and progressive muscle relaxation for post-chemotherapy patients. The design of this research uses a case study design. This case study research was conducted at Prof. Dr. Margono Soekarjo Purwokerto Hospitalin the Wijaya Kusuma room for post-chemotherapy patients, namely Mrs. M who had complaints of nausea and vomiting after chemotherapy. This research was conducted during 3 days of care from 30 January 2024 – 01 February 2024. Data was obtained from interviews, direct observation and nursing documentation. The instruments used were assessment sheets and nursing care notes. The results of the patient's research showed that the nausea was reduced unlike previous chemotherapy cycles, the patient was also able to consume 5-6 tablespoons of food. The conclusion is that there is an effect of deep breathing relaxation and progressive muscle relaxation in reducing nausea in cancer patients after chemotherapy.